THE INFLUENCE OF HEUTAGOGY IN MEASURING THE EFFECTIVENESS OF STUDENT LEARNING (Jurnal Tahsinia, 2024)
The importance of effective education is increasing in the era of globalization and advanced technology. Heutagogy, as an independent learning approach, offers solutions to increase student independence and learning capabilities. The background to this approach is based on the need for an educational model that is more adaptive and responsive to individual needs in a rapidly changing society. The aim of this study is to measure the effectiveness of heutagogy in improving student learning outcomes at STEBIS Bina Mandiri. This research identifies a gap in the literature, namely the lack of empirical research examining the effectiveness of heutagogy in Indonesian educational institutions. The application of heutagogy in the context of Indonesian education, which has not been widely researched. The methods used include surveys and qualitative analysis of data collected through interviews and observations. This study reveals that heutagogy helps students develop critical and reflective skills that are important for lifelong learning. In addition, this approach increases student learning motivation through a more personalized and student-centered learning experience. This research shows that heutagogy is effective in improving the quality of learning at STEBIS Bina Mandiri. The implementation of heutagogy not only supports better academic achievement, but also fosters learning independence which is an important competency in the 21st century.
Keywords: Heutagogy; Learning Effectiveness; Student Independence